The SWISS-MODEL Repository—new features and functionality. Issue Volume 45:Issue D1(2017) (28th November 2016) - Bienert, Stefan; Waterhouse, Andrew; de Beer, Tjaart A. P.; Tauriello, Gerardo; Studer, Gabriel; Bordoli, Lorenza; Schwede, Torsten
Abstract: SWISS-MODEL Repository (SMR) is a database of annotated 3D protein structure models generated by the automated SWISS-MODEL homology modeling pipeline. It currently holds >400 000 high quality models covering almost 20% of Swiss-Prot/UniProtKB entries. In this manuscript, we provide an update of features and functionalities which have been implemented recently. We address improvements in target coverage, model quality estimates, functional annotations and improved in-page visualization. We also introduce a new update concept which includes regular updates of an expanded set of core organism models and UniProtKB-based targets, complemented by user-driven on-demand update of individual models. With the new release of the modeling pipeline, SMR has implemented a REST-API and adopted an open licencing model for accessing model coordinates, thus enabling bulk download for groups of targets fostering re-use of models in other contexts. SMR can be accessed at https://swissmodel.expasy.org/repository .